ICT-Based Literacy Evaluation in Nigeria Educational Sector: Case Study in Kwara State - Olalekan BOLAJI, Hammed; Bilikis IBRAHIM-RAJI, Tinuke (Universitas Komputer Indonesia, 2023)
ICT is now a necessity for both professionals and organizations due to its pervasiveness across all fields of human endeavour. The literacy skills level plays a major role in its application for routine responsibilities and the pace at which task is complemented. For efficient service delivery in the public service, this study evaluated the ICT literacy abilities and their application among the staff of education agencies. It used a descriptive cross-sectional survey design. Structured items on the ICT skills assessment and utilization questionnaire (ICTSAUQ) were administered to fifty staff using convenient sampling techniques. To respond to the research questions posed by this study, descriptive and inferential statistics were used. The question was addressed using percentage means and standard deviations, and the questions were analysed using a t-test. The results showed that having a basic understanding of ICT helps do administrative tasks daily. However, the staff of the education agencies lacked the necessities for their daily routine of managerial responsibilities and operations. Hence, it was suggested that staff of the Education Agencies in Kwara State must be exposed to the required ICT skills to perform the routine functions at the optimal level. Additionally, it was suggested that agency staff members be encouraged to consistently improve their ICT literacy abilities through self-training and group work to improve the competence of service delivery in the educational sector